Understanding teachers' professional learning needs: what does it mean to teachers and how can it be supported?. Issue 7 (16th November 2020) - Cooper, Rebecca; Fitzgerald, Angela; Loughran, John; Phillips, Michael; Smith, Kathy
ABSTRACT: Professional learning is a significant focus of discussion in most schools but it is not all that common for these conversations to be informed by teachers' needs and expectations. Instead, they tend to be driven by external factors, such as accreditation, mandated professional development requirements and policies. Based on an in-depth study of a large number of teachers at one school, this paper begins to unpack the participants' views about and the expectations they hold for their professional learning. Data were collected over two school terms through several focus group interviews reaching approximately two-thirds of the staff. Analysis of the data sets led to identification of themes used to categorise teachers' perceived areas of developmental need (e.g. special needs, wellbeing, etc.) and what would be required to address these needs (e.g. time, collaboration, etc.). Findings indicate that what teachers receive to support their professional learning is not always what they want or value. Their aspirations regarding their professional learning needs tend to be more informed by their own beliefs about learning and teaching rather than more global, systematic or operational requirements.